The validity and reliability properties of a Persian version of the evidence-based practice profile (EBP2) questionnaire among Iranian students of health-related fields - Rezvan Elahifar; Mohammad Mahdi Parvizi; Hossein Fatemian; Mahsa Moosavi; Mitra Amini (BMC Medical Education)
Abstract Background Evidence-based medicine is defined as searching for medical information, reviewing and comparing it to each patient’s situation, and then judging the optimal decision. We aimed to measure the psychometric properties of the Evidence-Based Performance Profile (EBP2) Questionnaire among the students of health-related fields at Shiraz University of Medical Sciences. Methods This cross-sectional study was conducted in 2021. The EBP2 questionnaire, which includes 74 five-Likert-scale items, was translated into the Persian language using the forward-backward translation method. A panel of five experts approved the face, content, and structural validity of the questionnaire. The Cronbach’s alpha and McDonald’s Omega coefficients were utilized to assess the questionnaire’s internal consistency. Furthermore, both confirmatory and exploratory factor analyses were used to assess the questionnaire’s construct validity. SPSS software version 25 and LISREL software version 8.8 were used for statistical analysis. Results Overall, 339 students participated in this study. The cultural adaptability, linguistic equivalence, and content validity of the Persian version of the EBP2 questionnaire were approved by a five-member team of medical experts. In addition, the results showed excellent internal consistency of the Persian version of the EBP2 questionnaire (Cronbach’s alpha = 0.962, McDonald’s Omega (ML) = 0.963). Moreover, all domains had acceptable reliability (> 0.7), except the Practice domain which had a marginally acceptable Cronbach’s alpha coefficient equal to 0.686. Exploratory factor analysis discovered six domains for the questionnaire. Moreover, the confirmatory factor analysis demonstrated that all indices except the comparative fit index (CFI) and adjusted goodness of fit (AGFI) confirmed the validity of the EBP2 questionnaire. Conclusion The study’s findings indicate that the Persian translated of the EBP2 questionnaire exhibited satisfactory validity and reliability for assessing students’ evidence-based performance in health-related fields.